Intra-speaker phonetic micro-variation, and its relationship to phonetic and phonological change - Florent Chevalier (Anglophonia)
This paper looks at intra-speaker phonetic micro-variation patterns in four dyads, recorded in the 1980s in the working-class community of Glasgow. We present the importance of this kind of interaction-based variation in sociolinguistic studies, since short-term speech accommodation is considered to be one of the mechanisms for community-level sound change over time. We consider two examples of sound change which have taken place in vernacular Glaswegian English, one phonetic (vowel quality) and one phonological (vowel quantity). We predict that intra-speaker variation in quality and timing alternations for /i/ and /ʉ/ during conversations will reflect the trajectory of real-time sound change, and that this variation will relate to convergence towards the speakers closest to the future norm. Our results do not validate these hypotheses; however, they highlight the relevance of unresolved issues about the very nature of speech accommodation and the role played by social factors such as speaker age.